Synthesis of mesoporous hydroxyapatite through a soft template route using non-ionic surfactant. - Cheah, Wee-Keat (Asean Engineering Journal)
Conventional synthesis of mesoporous hydroxyapatite (HAp) commonly employs co-precipitation method using cationic surfactants such as CTAB. Such surfactants are expensive and crate tinier mesopores without an interconnecting pore structure. Using non-ionic surfactants in the synthesis of mesoporous HAp, the pore formation could be induced to tailor desirable pore characteristics. This paper reports on synthesis of mesoporous HAp through soft template route using non-ionic surfactants P123, F127 and P123/F127. Calcination was carried out at 550 degree celcius for 6 hours to reveal pores through the removal of the organic surfactant. The formation of HAp prior and subsequent to the calcination was evaluated through several materials characterization techniques. The X-ray diffraction (XRD) diffractograms revealed characteristic peaks of HAp corresponds to a typical HAp crystal phase, whereby a hexagonal lattice structure was deduced. SEM micrographs revealed rod-like HAp particles with diameter of approximately 24 nm and length ranging from 100 nm. TEM revealed the formation of nanopore channels within the rod-like structure, aligned in a lengthwise direction within the rods. The nanopore channels were consistent with the cavities being generated by the removal of non-ionic surfactant. The pores formed were found to be randomly distributed within the HAp structure.